BAND ALIGNMENT OF ULTRATHIN GIZO/SiO2/Si HETEROSTRUCTURE DETERMINED BY ELECTRON SPECTROSCOPY (Makara Journal of Science, 2011)
Amorphous GaInZnO (GIZO) thin films are grown on SiO2/Si substrate by the RF magnetron sputtering method. By the combination of measured band gaps from reflection energy loss spectroscopy (REELS) spectra and valence band from X-ray photo-electron spectroscopy (XPS) spectra, we have demonstrated the energy band alignment of GIZO thin films. The band gap values are 3.2 eV, 3.2 eV, 3.4eV and 3.6eV for the concentration ratios of Ga: In: Zn in GIZO thin films are 1:1:1, 2:2:1, 3:2:1 and 4:2:1, respectively. These are attributed to the larger band gap energy of Ga2O3 compared with In2O3 and ZnO. The valence band offsets (ΔEv) decrease from 2.18 to 1.68 eV with increasing amount of Ga in GIZO thin films for GIZO1 to GIZO4, respectively. These experimental values of band gap and valence band offset will provide the further understanding in the fundamental properties of GIZO/SiO2/Si heterostructure, which will be useful in the design, modeling and analysis of the performance devices applications